USING GAMIFICATION IN ENGLISH LESSONS (Scientific journal of the Fergana State University, 2023)
Schools today face significant challenges in terms of student motivation and engagement. One of the main goals of using game elements in education is to increase the level of motivation for learning due to external factors. It is noted that the use of gamification in education increases the learning motivation of students by creating their interest in achieving educational goals with the help of game-specific elements. The article highlights the levels of application of gamification in learning activities, the benefits of gamification in learning, which contribute to improving the quality of learning. In pedagogical practice, one can choose the required level of gamification depending on the educational need. Gamification, or the inclusion of game elements in non-game settings, provides an opportunity to help schools solve these problems. However, if gamification is to be useful for schools, we need to better understand what gamification is, how it works, and why it can be useful.